2020
DOI: 10.1021/acs.inorgchem.0c02103
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Tuning of the Electronic Structure of Mo2C by P and Ni Codoping for Optimizing Electrocatalytic Hydrogen Evolution

Abstract: Developing earth-abundant and highly efficient nonprecious metal catalysts for hydrogen evolution reaction (HER) is critical for the storage and conversion of renewable energy sources. Molybdenum carbide (Mo 2 C) has been extensively investigated as one of the most promising nonprecious electrocatalysts for boosting HER because of its low cost, high electrical conductivity, good chemical structure, and similar electronic structure to that of Pt. However, Mo 2 C always exhibits the negative hydrogenbinding ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 56 publications
0
19
0
1
Order By: Relevance
“…In particular, P-doping reduces the density of the empty d-bands in Mo 2 C and therefore attenuates the strength of the Mo–H bond. 19–21 Furthermore, N, P dual-doped Mo 2 C/porous carbon fiber composites exhibited good HER performance in 0.5 M H 2 SO 4 and 1.0 M KOH. 5 Besides, Chi et al 19 prepared a catalyst with Mo 2 C and MoP encapsulated into N, P co-doped carbon shells, which exhibited good HER performance in basic and neutral media with η 10 (the overpotential to afford the current density of 10 mA cm −2 ) values of only 169 mV and 228 mV, respectively.…”
Section: Introductionmentioning
confidence: 95%
“…In particular, P-doping reduces the density of the empty d-bands in Mo 2 C and therefore attenuates the strength of the Mo–H bond. 19–21 Furthermore, N, P dual-doped Mo 2 C/porous carbon fiber composites exhibited good HER performance in 0.5 M H 2 SO 4 and 1.0 M KOH. 5 Besides, Chi et al 19 prepared a catalyst with Mo 2 C and MoP encapsulated into N, P co-doped carbon shells, which exhibited good HER performance in basic and neutral media with η 10 (the overpotential to afford the current density of 10 mA cm −2 ) values of only 169 mV and 228 mV, respectively.…”
Section: Introductionmentioning
confidence: 95%
“…[19][20][21][22][23][24][25][26][27][28][29] Among the reported transition metal compounds, Mo 2 C has become a hot research spot due to its satisfactory HER activity derived from the special d-band electronic structures similar to that of Pt. [30][31][32][33][34][35] Aiming at increasing the HER performance, various attempts have been made to design the desired Mo 2 C catalysts, such as doping, [31][32][33][35][36][37][38] morphology optimization 4,10,31,39 and heterostructure engineering. [40][41][42][43][44] Generally speaking, the strong Mo-H binding energy impedes the desorption of active hydrogen to release H 2 , resulting in inferior HER performances of the Mo 2 C surface.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, N, S and P non-metal heteroatoms have been introduced into Mo 2 C to tune its high-density empty d-orbits, resulting in a suitable hydrogen adsorption energy to alleviate hydrogen atom desorption propitious to boost HER activity. 1,19–22 Moreover, delicate doping of metal heteroatoms (Fe, 13 Co 5 and Ni 14 ) with a small amount into Mo 2 C also can effectively promote the hydrogen adsorption and evolution. Specifically, the modulation of electronegativity, closely related with rich electrons from metal heteroatoms mentioned above, will bring Mo 2 C a favorable Mo–H adsorption energy by offering partial electrons from metal heteroatom to Mo atom in order to lower the unoccupied d-orbitals of Mo.…”
Section: Introductionmentioning
confidence: 99%
“…20 On the other hand, P doped Mo 2 C and Ni, P co-doped Mo 2 C also possess excellent HER activity. 21,22 Thus, beneficial electron interaction could be expected in Mn, P co-doped Mo 2 C. However, few studies on Mn, P co doped Mo 2 C have been reported.…”
Section: Introductionmentioning
confidence: 99%